Exploring Muslim Travelers’ Motives through Netnography: The Image of Non-Muslim Cultural Destinations and Halal Culinary Tourism at Pantai Indah Kapuk 2 - Fajrini, Nurkhalila; Yulia, Irla (Universitas Ahmad Dahlan, 2025)
The growing trend of Muslim travelers exploring non-Muslim destinations highlights new challenges in understanding how communication and perception shape travel decisions. This study examines the factors influencing Muslim tourists' intention to visit non-Muslim cultural destinations, with a particular focus on halal culinary tourism at Pantai Indah Kapuk 2 (PIK 2), Jakarta. Employing a netnography approach guided by the Theory of Planned Behavior (TPB), this research was conducted over six months (January-June, 2024) through virtual observation, online interviews, and qualitative content analysis of Instagram and TikTok posts related to halal culinary experiences. The findings reveal three major determinants of visiting intention: the accessibility of halal information, credibility of peer reviews and influencer recommendations, and the presence of Muslim-friendly cultural representations that enhance comfort and trust. Social media functions as a participatory communication space in which destination images and halal narratives are co-created through user-generated content, thereby influencing travelers’ attitudes, social norms, and perceived behavioral control. The study concludes that digital narratives play a central role in shaping Muslim travelers’ behavioral motives toward non-Muslim destinations. These results provide practical implications for destination managers and tourism marketers to design Muslim-friendly communication strategies, and highlight the urgency for future research to explore digital engagement and intercultural inclusivity in halal tourism development. Insights for destination managers and tourism marketers to design Muslim-friendly and communication-based promotional strategies for halal tourism development.